Influence of long‐stay jugular catheters on hemostatic variables in healthy dogs. Issue 5 (3rd July 2021) - Kielb Basile, Jessica L.; Lynch, Alex M.; Ruterbories, Laura; Castaneda, Kady; Griffith, Emily; Ueda, Yu
Abstract: Objective: To compare hemostatic variables performed on blood samples obtained from indwelling jugular catheters or direct venipuncture over a 72‐hour period. Design: Prospective experimental study. Setting: University research laboratory. Animals: Five healthy neutered male purpose‐bred Beagle dogs. Interventions: Each dog was sedated to facilitate placement of a long‐stay 20‐Ga polyurethane IV catheter into the jugular vein. Blood samples were obtained from the preplaced catheters at 4 time points corresponding to 0, 24, 48, and 72 hours relative to placement. Blood samples were also obtained by direct venipuncture of a peripheral vein using a 21‐Ga butterfly catheter and evacuated blood tubes at the same time points. Platelet count, platelet closure time, prothrombin time, activated partial thromboplastin time, fibrinogen, and kaolin‐activated thromboelastography were performed on these paired samples at each time point. The patency of the indwelling catheters was maintained by flushing every 6 hours with heparinized saline. Measurements and Main Results: No significant differences were identified in any of the hemostatic variables obtained by either blood collection technique at any time point during the study ( P  > 0.05). There was also no significant day‐to‐day variation in any catheter‐derived hemostatic variable obtained from individual dogs identified over the course of the study. Conclusions: These data suggest that accurate hemostatic variables may be obtained using blood collected from indwelling jugular catheters, maintained with heparinized saline for at least 72 hours, in healthy dogs.